Lifestyle and Chronic Pain across the Lifespan: An Inconvenient Truth?. Issue 4 (21st October 2019) - Nijs, Jo; D'Hondt, Eva; Clarys, Peter; Deliens, Tom; Polli, Andrea; Malfliet, Anneleen; Coppieters, Iris; Willaert, Ward; Tumkaya Yilmaz, Sevilay; Elma, Ömer; Ickmans, Kelly
Abstract : Chronic pain has a tremendous personal and socioeconomic impact and remains difficult to treat. Therefore, it is important to provide an update on the current understanding regarding lifestyle factors in people with chronic pain across the lifespan. Lifestyle factors such as physical (in)activity, sedentary behavior, stress, poor sleep, unhealthy diet, and smoking are associated with chronic pain severity and sustainment. This applies to all age categories, that is, chronic pain across the lifespan. Yet current treatment options often do not or only partly address the many lifestyle factors associated with chronic pain or attempt to address them in a standard format rather than providing an individually tailored multimodal lifestyle intervention. The evidence regarding lifestyle factors is available in adults, but limited in children and older adults having chronic pain, providing important avenues for future research. In conclusion, it is proposed that treatment approaches for people with chronic pain should address all relevant lifestyle factors concomitantly in an individually‐tailored multimodal intervention. Ultimately, this should lead to improved outcomes and decrease the psychological and socioeconomic burden of chronic pain. Level of Evidence: IV.